INTERSECTION ARRANGEMENT DESIGN ON SULTAN HAMID II ROAD - GUSTI SITUT MAHMUD ROAD "“ 28 OKTOBER ROAD "“ SELAT PANJANG ROAD PONTIANAK DUE TO THE OPERATION OF THE LANDAK PARALLEL BRIDGE - Lo, Oktaviani Chelin; Mukti, Elsa Tri; Juniardi, Ferry (Jurnal Teknik Sipil, 2023)
The signalized intersection on Sultan Hamid II Road - Gusti Situt Mahmud Road "“ 28 Oktober Road "“ Selat Panjang Road is an intersection in Pontianak city with high traffic problems. The construction of the Landak parallel bridge initially aimed to reduce congestion, but this created an imbalance that caused congestion. This research analyses the performance of the intersection using the 1997 Indonesian Road Capacity Manual method and VISSIM software simulation. Data was collected in the form of intersection geometric data, traffic light cycle time, vehicle speed, and traffic volume taken for three days with a survey tool in the form of CCTV as a recorder at 06.00 - 18.00 WIB. Then, the data collected is processed into the basis of research to calculate the performance of the intersection in existing conditions and develop alternative improvement plans using MKJI 1997 and VISSIM software simulations. In the analysis with the MKJI 1997 method, the North road's service level is LOS C; the East road is LOS C; the South road is LOS B; the West road is LOS F, and the highest degree of saturation is 1.56. Analysis with VISSIM software simulation obtained the level of service of the intersection LOS C. After making alternative changes in cycle time, geometrics, and restrictions on the time of prohibition of passing obtained in alternative 15 with changes from signalized intersections to roundabouts and geometric changes.